Pancasila as a Paradigm in Shaping Communication Ethics in the Digital Age - Martya Putri, Bernadeta Aprilla; Anindya, Nasywa Alif; Zahirotul Hikmah, Cindy Noor Laila Zahirotul Hikmah; Muchtar, Putri Fadhilla; Sulistianingsih, Dewi (Indonesia Media Law Review, 2025)
Developments in the digital era have changed the way people communicate, especially through social media. Nowadays, communication can be done freely, but this freedom is actually abused by many people to cause several problems, such as hoaxes, privacy violations, and even hate speech. Therefore, the purpose of this study is to analyze the role of Pancasila education in shaping civilized ethics in the digital era. This research uses a descriptive qualitative method with a literature study approach, namely analyzing and collecting data through various sources, such as journals, scientific articles, and books that are still relevant to the topic discussed. The results show that the values contained in Pancasila are very important to be used as digital ethics. This research also shows that digital literacy and the implementation of Pancasila values in communication ethics in Indonesia are low. In contrast, Finland has high digital literacy and their readiness to add ethical teachings into their curriculum since early childhood education. Solutions offered include the implementation of Pancasila values into the curriculum from an early age as well as campaigns or calls that emphasize the importance of polite communication and respect for everyone's privacy.